Association of Oral Tobacco-Free Nicotine Delivery Product with Acute Renal Tubular Necrosis - Ratna Acharya; William Clapp; Kiran Upadhyay (Medicina)
Usage of novel non-tobacco oral nicotine delivery products (ONDPs) has been increasing among adolescents in the United States. It is presumed that they are less toxic than their tobacco-containing counterparts, but that has not been examined in controlled studies. Most of the studies have focused on non-renal manifestations of tobacco consumption via different means. The renal manifestations of non-tobacco ONDPs are not very well known, especially in immunocompromised patients. A 19-year-old male transplant recipient presented with flank pain and a few days’ history of intake of ZYNR pouches. Immunosuppression was with tacrolimus, mycophenolate, and steroids. Baseline serum creatinine was 1.1–1.3 mg/dL. Laboratory evaluation showed elevated C-reactive protein, increased serum creatinine and blood urea nitrogen, leukocytosis, neutrophilia, and increased lactate dehydrogenase (LDH). Infectious disease work-up was negative. A kidney transplant biopsy showed severe acute tubular injury/necrosis (ATN) without evidence of rejection. Donor-specific antibodies were negative. Other etiologies of hemolysis were negative. He did not require renal replacement therapy. Kidney function and LDH improved gradually. The most recent follow-up eight months after presentation showed a serum creatinine level of 2.6 mg/dL with stable electrolytes, with eGFR of 35 mL/min/1.73 m2. Here, we describe a 19-year-old adolescent with a kidney transplant who sustained ATN leading to advanced chronic disease apparently following the usage of non-tobacco ONDP. Further larger studies are needed to study ATN as a possible renal manifestation of these next-generation products to raise awareness among the public.